The effect of space utilization under the ground-mounted solar farm on power generation - M Kumpanalaisatit; A Jankasorn; W Setthapun; H Sintuya; SN Jansri (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2019)
The ground-mounted solar farms are the most common type of Thailand solar power plant. Presently, the area under the solar panels in Thailand had not been utilized. This work was to investigate a suitable configuration for space utilization under the PV panels which could promote power production. The effect of space utilization was investigated for 3 configurations: a water pond, chili cultivation, and a grass plantation. Under the first PV string, the pond sizing 2.4 × 15 meter was created. Under the 2nd PV string, 60 chilies samples were planted. Moreover, the grass was planted under the third string. The intensity of solar radiation (W/m2), temperature, voltage and current of solar panels were also monitoring. The impact of all configurations on the power generation was evaluated and compared with a control. Results indicated that the space utilization of the first string (the pond) and of the second string (the chili cultivation) generated electricity at 1.6 kW. Both configurations could generate more power than control. The pond and the vegetable plantation were suitable configurations for promoting power production.